Two-dimensional background field gravity: A Hamilton-Jacobi analysis - Bertin, M. C.; Pimentel, B. M. [UNESP]; Valcarcel, C. E. [UNESP] (American Institute of Physics (AIP), 2012)
We analyse the constraint structure of the background field model for two-dimensional gravity via the Hamilton-Jacobi formalism. This analysis consists in finding the complete set of involutive Hamiltonians that assure the integrability of the system. We then calculate the characteristic equations of the system, also establishing the equivalence between these equations and the field equations. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4748301]